Determinants of Financial Inclusion and Financial Well-Being of MSMEs Entrepreneurs in Lamandau Regency - Nurlina, Siti; Diky Paramitha (Journal of Financial and Behavioural Accounting, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are an important sector in the Indonesian economy, contributing greatly to job creation and economic growth. Financial inclusion and financial well-being of MSMEs entrepreneurs are important factors in improving the performance and competitiveness of MSMEs. The objective of this study is to examine the factors that influence financial inclusion and financial well-being. There are four independent variables tested, namely financial literacy, accessibility, affordability, and use. This study was conducted in Lamandau Regency, Central Kalimantan Province, Indonesia. The sample of this study was MSMEs entrepreneurs in Lamandau Regency, Central Kalimantan Province. Data were collected through questionnaires and processed using the smart-PLS application. The questionnaire was distributed to the MSMEs communication forum in the form of an e-form. The results of this study indicate that the factors that influence financial inclusion and financial well-being are financial literacy. The conclusion of this study is that financial literacy is a determining factor in financial inclusion and ultimately affects financial well-being. These results provide recommendations for the government to play an active role in providing financial education to the public, especially MSMEs entrepreneurs